Genetic diversity of Ganoderma in oil palm plantings - Miller, R.N.G.; Holderness, M.; Bridge, P.D.; Chung, G.F. (British Society for Plant Pathology, 1999)
Isolates of Ganoderma spp. associated with basal stem rot of oil palm were obtained by sampling from two palm plantings in Malaysia. Members of a subset of these were compared using a combination of somatic incompatibility and molecular genetic analyses. Incompatibility interactions between heterokaryons in culture indicated that Ganoderma generally occurred as numerous distinct strains, with compatible strains usually confined to individual palms. Analysis of restriction fragment length polymorphisms (RFLPs) in presumptive mitochondrial DNA (mtDNA) revealed heterogeneity among isolates from neighbouring palms, and from within individual palms. The combination of mtDNA variability and somatic incompatibility suggests that Ganoderma BSR does not spread by direct root-to-root contact between palms. The results may indicate infection spread through basidiospore dispersal or through contact with a heterogenous long-term residual inoculum in debris.